World Bank East Asia and Pacific Economic Update, October 2020 : From Containment to Recovery - World Bank (Washington, DC: World Bank, 2020)
COVID-19 has delivered a triple shock to the developing East Asia and Pacific (EAP) region: the pandemic itself, the economic impact of containment measures, and reverberations from the global recession. Without action on multiple fronts, the pandemic could reduce regional growth over the next decade by 1 percentage point per year, with the greatest impacts being felt by poor households, because of lower levels of access to healthcare, education, jobs, and finance. Why were many economies in the region able to contain the disease while some others still struggle? How have these shocks affected economic activity and poverty in different countries? What are the prospects for recovery and how will longer term growth be affected across the region? Is there a tension between containing the disease and providing relief today and promoting recovery and growth tomorrow? These key questions are addressed in the World Bank’s October 2020 EAP Economic Update.